Importance of Forensic Odontology (Indian Journal of Forensic Medicine & Toxicology, 2020)
Forensic dentistry is the connection between the dental professions and forensic professions. In fact, the teethand jaws are highly resistant to degradation and decomposition by postmortem. For a number of differentreasons and situations such as mass disasters, in criminal investigations and in the case of disfigured bodiesdue to fire and vehicle accidents, dental identification of humans happens. The different methods includex-rays, antemortem & post-mortem photographs, tooth prints, palatal rugae, lip printing, bite marking andmolecular methods such as polymerase chain reaction for pulp DNA analysis.
Keywords: forensic, bite mark, lip print, tongue print, polymerase chain reaction